RUMAH TINGGAL DALAM AL-QUR’AN: Analisis Term Al-Bait dan Al-Maskan dalam Al-Tashîl Li Ta’wîl Al-Tanzîl Karya Mushthafâ Ibn Al-‘Adawî - Rahendra Maya; Hidayati Hidayati; Syaeful Rokim; Muhammad Fadilah Alfarisi (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
In the verses of the Qur’an, the concept of a house in general and a residence or permanent residence is often mentioned using several terms, including the terms al-bait or al-buyût and al-maskan or al-masâkin with various forms of derivations. This reality attracts the attention of interpreters to study it through their interpretations in their tafsir works. Among them is Mushthafâ ibn Al-‘Adawî, an Egyptian scholar who has a general science background in his tafsir work entitled Al-Tashîl li Ta’wîl Al-Tanzîl: Al-Tafsîr fî Su’âl wa Jawâb using the question-and-answer method. By using qualitative methods through a descriptive-qualitative literature study approach with data collection techniques using literature sources and documentation studies with descriptive-interpretive data analysis techniques through content analysis, this article uses data sources The primer is the book Al-Tashîl li Ta’wîl Al-Tanzîl: Al-Tafsîr fî Su’âl wa Jawâb by Mushthafâ ibn Al-‘Adawî. Mushthafâ ibn Al-‘Adawî in his interpretation of the terms al-bait and al-maskan in the Al-Qur’an does not seem to really differentiate the nature and accentuation of the meaning of the two terms, except in his interpretation of Q.S. Al-Nahl [16]: 80. If it is considered different, then Mushthafâ ibn Al-‘Adawî stated that al-bait is stated as a residence or permanent residence in a nomadic or sedentary lifestyle, it functions as a place to spend the night or rest at night, while al-maskan is a house that functions as a bringer of peace for its residents.